2020
DOI: 10.3390/nano10030473
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanostructures with Antibacterial Properties Prepared by a Green Electrochemical-Thermal Approach

Abstract: Zinc oxide (ZnO) nanostructures are widely applied materials, and are also capable of antimicrobial action. They can be obtained by several methods, which include physical and chemical approaches. Considering the recent rise of green and low-cost synthetic routes for nanomaterial development, electrochemical techniques represent a valid alternative to biogenic synthesis. Following a hybrid electrochemical-thermal method modified by our group, here we report on the aqueous electrosynthesis of ZnO nanomaterials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Meanwhile, various electrochemical processes for synthesis of ZnO NPs/MPs have been reported including electrodeposition [ 39 , 40 ], sacrificial anode electrolysis [ 41 ], and electrochemical deposition under oxidizing conditions (EDOC) [ 42 , 43 ]. Hybrid techniques of electrochemical-thermal processes were also reported in aqueous environment [ 44 , 45 ]. In electrodeposition, ZnO thin films can be produced controlling current density, applied potential, time, and electrolytic bath concentration as major operating parameters using zinc nitrate solution or zinc chloride solution as precursors [ 40 ].…”
Section: Characteristics Of Zno Materials Based On Synthesis Technmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, various electrochemical processes for synthesis of ZnO NPs/MPs have been reported including electrodeposition [ 39 , 40 ], sacrificial anode electrolysis [ 41 ], and electrochemical deposition under oxidizing conditions (EDOC) [ 42 , 43 ]. Hybrid techniques of electrochemical-thermal processes were also reported in aqueous environment [ 44 , 45 ]. In electrodeposition, ZnO thin films can be produced controlling current density, applied potential, time, and electrolytic bath concentration as major operating parameters using zinc nitrate solution or zinc chloride solution as precursors [ 40 ].…”
Section: Characteristics Of Zno Materials Based On Synthesis Technmentioning
confidence: 99%
“…In EDOC, sacrificial anodic oxidation, cathodic reduction, and oxidation processes were involved for the synthesis of spherical ZnO NPs (9 nm) [ 42 ]. Hybridizing electrochemical and thermal approaches, ZnO NPs/MPs were synthesized in aqueous sodium bicarbonate solution, generating zinc hydroxide species and further oxidized to ZnO in calcination process at >300 °C [ 44 , 45 ]. Specifically, anionic or cationic stabilizers can be used to tune physicochemical properties of ZnO NPs/MPs including morphology and particle size.…”
Section: Characteristics Of Zno Materials Based On Synthesis Technmentioning
confidence: 99%
See 1 more Smart Citation
“…Elongated submicrometer rice-grain structures (with length around 1 µm) could be obtained preparing the colloids at 80 • C with CTAB and calcining them at 300 • C [14] (Figure 2a). PDDA, after overnight drying at 120 • C, promoted the formation of wire-like microstructures, with a major length of 300-500 nm; growth lines moving along the wires suggested that these structures grew by lamellar superimposition [15] (Figure 2b). The use of PSS resulted in spheroidal NPs, with an average diameter around 50 nm, which aggregated in micron-sized clusters after calcination at 600 • C (Figure 2c).…”
Section: Synthesis and Characterization Of Znonpsmentioning
confidence: 99%
“…Bearing in mind the recent growth in environmentally friendly and low-cost synthetic routes for nanomaterial synthesis, electrochemical techniques represent a valid alternative to biogenic synthesis. In this regard, the aqueous electrosynthesis of ZnO nanomaterials (both rod-like and flower-like structures) with different aspect ratios based on the use of alternative stabilizers such as benzyl-hexadecyl-dimethylammonium chloride (BAC) and poly-diallyl-(dimethylammonium) chloride (PDDA) has been reported [ 20 ]. The combination of UV–vis, FTIR, and XPS spectroscopies demonstrated the whole conversion of the raw colloidal materials into stoichiometric ZnO species with moderate morphological modification.…”
mentioning
confidence: 99%